Colonization profiles of gut microbiota in goat kids from neonatal to weaning period - Wu, Yuqin; Hou, Dunying; Zhan, Siyuan; Wang, Linjie; Cao, Jiaxue; Guo, Jiazhong; Li, Li; Zhang, Hongping; Niu, Lili; Zhong, Tao (Frontiers in Microbiology, 2024)
Understanding the colonization and change patterns of gut microbiota is pivotal for comprehending host health. As a newly cultured breed, the studies on the gut microbiota of Tianfu goats remain limited. This study aimed to address this gap by analyzing the microbial composition and colonization patterns of fecal samples collected from goat kids from birth to weaning. Fecal samples were collected on days 0, 7, 14, 21, 28, 35, 42, 49, 53, 55, 57, and 64, and the changes and colonization patterns of microorganisms were analyzed through high-throughput 16S rRNA sequencing. The results showed that the abundance of fecal microbiota in goat kids gradually increased over time, followed by a decrease after weaning and stabilization, with reduced individual differences. The colonization of fecal microorganisms mainly presented three different stages: days 0-14, days 21-49, and days 53-64. During the suckling period, the relative abundance of Proteobacteria (72.34%) was the highest, followed by Firmicutes (21.66%). From 21 days old, the microbiota in goat kids gradually to be diverse, with Lachnospiraceae and Ruminococcaceae being dominant.During post-weaning, Ruminococcaceae (30.98%-33.34%) was becoming prominence which helpful for cellulose decomposition. LEfSe analyzed three important time points (d0 vs d7, d7 vs d14, d49 vs d53, LDA score > 4 and p < 0.05), 53 microbial communities with stage differences were identified. Functional prediction using PICRUSt revealed that differential microbial communities are mainly related to carbohydrate and amino acid metabolism pathways. Overall, this study addresses the intricate relationship between ages, diets, and microbiota compositions in Tianfu goat kids, and also offering insights into microorganisms-host interactions.